Analisis Efektivitas Penggunaan Anggaran Belanja dalam Menilai Kinerja Keuangan Pada Dinas Pemadam Kebakaran dan Penyelamatan Kota Padangsidimpuan - Adelini Siagian; Hendra Harmain; Wahyu Syarvina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Abstract One of the government organizations tasked with managing affairs in its operational area in order to protect, be responsive, resolve, and rescue protected from fire is the Padangsidimpuan City Fire and Rescue Service. Performance is a term used to describe how well the implementation efforts in fulfilling the vision and mission of the organization. This research is in order to evaluate the effectiveness of the expenditure budget, namely from 2018 to 2022. The purpose of this budget capability evaluation is to assess the absorption of expenditure during the budget period. This study used a qualitative methodology combined with quantitative data collection and documentation methods. Descriptive analysis methods were used using efficiency ratios, expenditure growth analysis, operating expenditure and capital expenditure compatibility analysis, expenditure variance analysis. Based on the results of research using expenditure variance analysis, budget performance can be said to be good because there are no expenditures that exceed the budget. Analysis of expenditure growth between 2018-2022 shows positive growth. The findings of the expenditure conformity analysis show that operational costs use more of the expenditure budget than capital expenditure. In addition, with an average of 92.05%, the efficiency ratio of budget realization indicates that the use of the 2018-2022 budget is less efficient.